Do You Hear What I See: Learning Experiences of Black Men who are Deaf or Hard-of-Hearing - Mavis A. Clark (Adult Education Research Conference, 2002)
The purpose of this study is to examine how non-hearing adult Black male learners understand their learning and schooling experiences. In order to understand their educational experiences, I am reconceptualizing the triad race, gender, and class paradigm by introducing the notion of deafness. I bring to the fore, a discussion on positionality and identity development as it relates to nonhearing adult Black male learners within the adult education context.